A Case of Syringomyelia with Back and Shoulder Pain - Hyun Young Choi; Jae Eun Jeong; Jae Sung Lee; Jang Mi Park; Cham Kyul Lee; Eun Yong Lee; Na Young Jo; Jeong Du Roh (MEDrang Inc., 2019)
The purpose of this study was to describe the treatment of the clinical symptoms of syringomyelia using Korean medicine. A patient with syringomyelia complained of back and shoulder pain, numbness of the upper right limb, headaches and dyspnea. He was treated with herbal medicine, acupuncture, moxibustion, and physical therapy. The Visual analog scale (VAS) was used to score sensory symptoms (pain, numbness) and Modified Borg scale (mBorg) was used to score dyspnea. After the treatment, his symptoms were relieved. The patient's chief complaint was back and shoulder pain which was reduced greatly from a VAS score of 6 between 1-2. The results in this study may contribute to the development of the Korean medicine field of syringomyelia in the future.